"A Black Spot": Florida's Crusade against Venereal Disease, Prostitution, and Female Sexuality During World War II - Troy Thompson (University of North Florida, 2005)
Long before there was HIV/AIDS, venereal disease constituted a challenge to public health officials. This paper captures some of the public health, educational, political, and law enforcement interventions attempted in Florida (and the Tampa Bay area in particular) around the time of the Second World War, reflecting herein the social beliefs and understandings of times past.